Նոր նյութեր խեթական տերության և հայկական լեռնաշխարհի երկրների փոխհարաբերությունների մասին - Քոսյան, Արամ («Զանգակ - 97»)
Düring the 1970's excavations at Ma* at Höyük (about 30km to the southeast of Zile, Central Asia Minor) was unearthed a significant archivc containing more than 100 letters written in Hittite cuneifonn Script. Among these letters one — Ma* at N. 96, refers to two political entities of the Armenian Highland — Hayasa and Isuwa. The paper rcpresents a füll publication of this leter with historical commentaries.
Keywords: Հայոց պատմություն